INFLUENCE OF GUT MICROBIOTA ALTERATIONS ON THE ONSET AND PROGRESSION OF CELIAC DISEASE (The Research of Medical Science Review, 2025)
The intestinal microbiota plays a pivotal role in the ontogeny and regulation of the mucosal immune system and may exert a protective influence against immune mediated pathologies. Celiac disease (CD), a chronic autoimmune enteropathy precipitated by the ingestion of gluten-containing proteins in genetically susceptible individuals, has been increasingly associated with dysbiosis perturbations in the gut microbial community structure. Emerging cross-sectional analyses delineating microbial profiles of CD patients versus healthy controls have uncovered significant compositional disparities; however, the causal relationship between microbiome alterations and disease etiology remains inadequately resolved. Experimental investigations employing bacterial isolates derived from individuals with CD have demonstrated that specific microbial taxa may potentiate aberrant immunological responses to gluten, exacerbating intestinal inflammation, whereas certain commensals appear to confer immunomodulatory or protective effects. Additionally, both host genetic predispositions—particularly HLA-DQ2/DQ8 haplotypes—and environmental exposures during early postnatal development have been correlated with early-life microbial colonization patterns and longitudinal microbiota trajectories that may influence CD susceptibility. Epigenetic regulatory mechanisms, including DNA methylation, histone modification, and non-coding RNAs, have also emerged as influential determinants of gut microbiota configuration and functional output. These mechanisms may serve as molecular mediators linking gene-environment interactions to microbiome-driven immuno pathogenesis in CD. This review synthesizes current evidence on the interplay between host genomics, environmental modulators, and epigenetic regulation in shaping gut microbial ecosystems and explores their collective implications for celiac disease onset, progression, and clinical management. A deeper understanding of these interdependent factors will inform the development of targeted microbiota-based therapeutic interventions and precision medicine approaches aimed at modulating host-microbe interactions to attenuate CD pathology.